2019
DOI: 10.1093/humrep/dez150
|View full text |Cite
|
Sign up to set email alerts
|

Declining realisation of reproductive intentions with age

Abstract: STUDY QUESTION What is the likelihood of having a child within 4 years for men and women with strong short-term reproductive intentions, and how is it affected by age? SUMMARY ANSWER For women, the likelihood of realising reproductive intentions decreased steeply from age 35: the effect of age was weak and not significant for men. WHAT IS KNOWN ALREADY Men an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 52 publications
2
34
1
2
Order By: Relevance
“…1 In developed countries, the increase in infertility may be attributable to environmental exposure and social changes, including a major trend of delaying parenthood to an age interval marked by higher risk of infertility. 2,3 In the United States, more than 1 in 10 women of reproductive age have ever used infertility services. 4 The Centers for Disease Control and Prevention have emphasized the need for the public health community to produce a more complete picture of infertility treatment use.…”
mentioning
confidence: 99%
“…1 In developed countries, the increase in infertility may be attributable to environmental exposure and social changes, including a major trend of delaying parenthood to an age interval marked by higher risk of infertility. 2,3 In the United States, more than 1 in 10 women of reproductive age have ever used infertility services. 4 The Centers for Disease Control and Prevention have emphasized the need for the public health community to produce a more complete picture of infertility treatment use.…”
mentioning
confidence: 99%
“…Both moving out of the parental home and forming a stable partnership have to be seen from a life course perspective, and are, therefore, age dependent. If people achieve certain conditions before or after they are in the range of ages for having children, as determined by normative and biological factors, it might have no influence on their fertility (Beaujouan et al 2019). The literature on transitions to adulthood has documented extensively how these transitions affect fertility (e.g., Baizán et al 2003), but it has not quantified how these transitions affect the crossnational differences in fertility rates we observe today.…”
Section: A Tentative Frameworkmentioning
confidence: 99%
“…For most Chinese families, childbearing is one of the most important functions of marriage and family. Considering the existing research, whether there is the influence of disease or not, people's fertility intention is strongly related to age, and questionnaire is mainly designed to understand the fertility intention of ADPKD patients and the cognition of PGT technology, so the control study with healthy people was not included in the study design [27,28]. This study showed that only 45.0% (117/260) of ADPKD patients at reproductive age had fertility intentions.…”
Section: Fertility Willingnessmentioning
confidence: 99%